Statement of the Ethics Committee of Turkish Medical Association on Disease Outbreaks - Ethical Committee, Turkish Medical Association (The Bulletin of Legal Medicine, 2020)
Communicable diseases and outbreaks have led to mass human morbidity and mortality throughout the history. Preventive health services are of essential importance in combating communicable diseases. Human intervention to the nature is causing even larger-scale destruction and outbreaks by disturbing natural life, ecological balance and ecosystems and existing inequalities. The most recent example is the on-going COVID-19 outbreak now defined as pandemic. Global outbreaks bring along radical changes ranging from daily life habits to political, economic and cultural structure of societies. These changes have their most adverse effects on disadvantaged groups. It is clear that such outcomes can be prevented through democratic and scientific interventions upholding the interests of people.